Diagnostic validity of optic nerve head colorimetric assessment and optical coherence tomography angiography in patients with glaucoma. Issue 7 (23rd July 2020) - Mendez-Hernandez, Carmen; Wang, Surina; Arribas-Pardo, Paula; Salazar-Quiñones, Liseth; Güemes-Villahoz, Noemi; Fernandez-Perez, Cristina; Garcia-Feijoo, Julian
Abstract : Background/Aims: The aim of this study was to assess the optic nerve head (ONH) and macular vessel density with optical coherence tomography angiography (OCT-A) and the ONH haemoglobin (ONH Hb) amount with Laguna ONhE program in open-angle glaucoma (OAG) patients. Methods: In this prospective observational cross-sectional study, 67 OAG patients and 41 healthy age-sex frequency matched subjects were examined with OCT-A and retinal photos. The circumpapillary (wcpVD), optic nerve head (iVD) and macular (wmVD) capillary vessel density of OCT-A and ONH colorimetric assessment to determine the ONH Hb amount using the Laguna ONhE program were evaluated. Results: Significant differences between normal subjects and glaucoma patients in the wcpVD (22.18±3.42 vs 16.03±2.89%; p<0.001), iVD (18.31±5.56 vs 12.52±4.67%; p<0.001), wmVD (15.60±2.34 vs 13.34±2.32%; p<0.001) and amount of ONH Hb (71.10±1.67 vs 68.86±2.46%; p<0.001) and in the papillary cup (68.14±5.25 vs 64.77±5.08%; p=0.001) were found. The Laguna ONhE glaucoma discriminant function (GDF) index had a negative value in the OAG patients and normal values in healthy subjects (−18.76±13.31 vs 7.98±14.09; p<0.001). The area under the receiver operating characteristic (ROC) curve (AUROC) for discriminating between healthy and glaucomatous eyes was highest for wcpVD (0.93; 95% CI 0.86 to 0.97, p<0.0001), followed by GDF (0.92; 95% CI 0.86 to 0.97, p<0.0001), iVD (0.79; 95% CI 0.70 to 0.86; p<0.0001) and ONH Hb (0.78; 95% CI 0.69 to 0.85, p<0.0001). Pair wise comparisons showed that the AUROC of wcpVD (0.93) was not significantly different than GDF (0.92) (p=0.855). Conclusion: Laguna ONhE program and OCT-A have similar diagnostic validity in open-angle glaucoma patients.